2020
DOI: 10.1159/000508035
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Children with Acute Rheumatic Carditis from a High-Incidence Region: Importance of Unexplained Worsening of Functional Class

Abstract: Background: Acute rheumatic fever (ARF) and acute rheumatic carditis (ARC) continue to be a major public health problem in developing countries. Objective: To study the characteristics of children with ARC being treated at a tertiary centre. Methods and Results: We studied 126 children (mean age 10.4 ± 2.3 years, range 5-15 years, 60% males) diagnosed with ARC by treating cardiologists. Most had lower socioeconomic status. Fifty of 126 (40%) presented with a first episode of ARC. Joint symptoms were present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…In previous studies, joint pain has been reported as the most common complaint. 16,26,27 Considering the physical examination findings, in our study, arthritis was the most common, followed by carditis, which is consistent with the literature findings. Similar to my study, in most studies with a small number of patients, except for one, erythema marginatum and subcutaneous nodules were not encountered.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, joint pain has been reported as the most common complaint. 16,26,27 Considering the physical examination findings, in our study, arthritis was the most common, followed by carditis, which is consistent with the literature findings. Similar to my study, in most studies with a small number of patients, except for one, erythema marginatum and subcutaneous nodules were not encountered.…”
Section: Discussionsupporting
confidence: 91%
“…In this issue of Cardiology , Narang et al [4] report the clinical presentation of 126 children with acute rheumatic fever who were treated in a tertiary medical center (60 patients had a previous history of rheumatic fever). Joint symptoms were present in 29% and fever in only 25% of the patients; 2.4% of the patients had subcutaneous nodules and there were no patients with erythema marginatum or chorea.…”
mentioning
confidence: 99%